Artificial Intelligence for Feeling Analysis in Video Games - García Regalado, Uriel; Carballo Valverde, Yenori (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Students from the State Distance University of Costa Rica develop video games then the feelings they transmit are evaluated. The objectives of this research are focused on determining a solution that, through artificial intelligence, automates its review. For this reason, relevant concepts are addressed, those that are related to Artificial Intelligence and its domain area: “Machine Learning”. Regarding the methodological framework, it is made up of agile methodologies that through its tools allow establishing a business plan and a solution model. Finally, conclusions and recommendations are detailed according to the results of the analysis.